2018
DOI: 10.1073/pnas.1714131115
|View full text |Cite
|
Sign up to set email alerts
|

Protonation state of inhibitors determines interaction sites within voltage-gated sodium channels

Abstract: Voltage-gated sodium channels are essential for carrying electrical signals throughout the body, and mutations in these proteins are responsible for a variety of disorders, including epilepsy and pain syndromes. As such, they are the target of a number of drugs used for reducing pain or combatting arrhythmias and seizures. However, these drugs affect all sodium channel subtypes found in the body. Designing compounds to target select sodium channel subtypes will provide a new therapeutic pathway and would maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 66 publications
(95 reference statements)
6
45
0
Order By: Relevance
“…Overall, the results by Buyan et al (17) provide accurate predictions about the binding mode of pore blockers and, for the first time, mechanistic insight about the differences between tonic and use-dependent blockers. Taken together, these predictions will help to design novel pore binders and to predict their behavior in future experiments.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…Overall, the results by Buyan et al (17) provide accurate predictions about the binding mode of pore blockers and, for the first time, mechanistic insight about the differences between tonic and use-dependent blockers. Taken together, these predictions will help to design novel pore binders and to predict their behavior in future experiments.…”
mentioning
confidence: 82%
“…Buyan et al (17) show that the results are robust with respect to the choice of the molecule (they consider three perpetually neutral and three titrable molecules) and are consistent for two VGSCs: one prokaryotic (NavMs) and the other eukaryotic (NavPas). Importantly, the novel binding site can explain the halogen electronic density measured by Bagnéris et al (18) by cocrystallizing NavMs with PF-5215786.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…As for the location, in silico docking revealed that unlike other sodium channel inhibitor molecules, riluzole was preferentially located within the fenestrations, and tended to avoid the central part of the pore or the vicinity of the selectivity filter, where it could interfere with conduction. Localization within the fenestration has been previously observed in molecular dynamics simulations investigating the general anesthetic isoflurane 24 and propofol 25 , as well as the local anesthetic benzocaine [26][27][28] and lidocaine (neutral form) 29 , but it has never been found to be the dominant position. The unusual location predicted by in silico docking is supported by the way riluzole acted in experiments.…”
Section: Discussionmentioning
confidence: 96%
“…Sodium channel pores are small in diameter (~4.1 Å), water-filled (Courtney, 1987;Payandeh et al, 2011) and narrow toward the selectivity filter (Heinemann et al, 1992;Favre et al, 1996) suggesting sodium channel pores "restrict" drug blockerbinding interactions. Recently, Buyan et al (2018) conducted a molecular dynamics examination of the binding of six compounds (three electrically neutral and three existing in neutral and positively charged forms at pH 7.0) that block sodium channels. While both forms partition into the lipid bilayer, findings suggest the existence of two possible binding sites.…”
Section: Discussionmentioning
confidence: 99%